Partnership Health Check Up - Low, Jan W. (International Potato Center, 2023)
The purpose of the “Partnership Health Check Up” is to encourage early and open communication on the partnership processes within the project, so that any concerns can be identified and addressed appropriately. This qualitative tool known “the Partnership Health Check-list” was developed in 2010 and has been used in many projects. In a concise way it asks each individual from key partner organizations to give their view on key factors that look at how the partnership is working. The tool uses a simple Liekert Scale for respondents to score their “satisfaction” level for different processes within the partnership.